Determination of Abnormal Returns from the Point of View of Environmental Performance In Mining Companies - Yunita, Nur Afni; juliani, Juliani; Naz'aina, Naz'aina; yusra, Muhammad (Jurnal Akuntansi dan Keuangan, 2024)
This research aims to examine the influence of environmental, social and governance on abnormal returns. The sample in this research are mining companies that disclosed ESG disclosure scores in 2020-2022. The sampling technique used was purposive sampling to obtain 45 companies that disclosed ESG disclosure scores for 3 consecutive years from 2020-2022. Testing in this research uses descriptive statistics and hypothesis testing. The results of this study show that environmentalism has no effect on abnormal returns. However, social and governance have a positive effect on abnormal returns